Effect of Periodic Granulocyte Colony-Stimulating Factor Administration on Endothelial Progenitor Cells and Different Monocyte Subsets in Pediatric Patients with Muscular Dystrophies - Andrzej Eljaszewicz; Dorota Sienkiewicz; Kamil Grubczak; Bożena Okurowska-Zawada; Grażyna Paszko-Patej; Paula Miklasz; Paulina Singh; Urszula Radzikowska; Wojciech Kulak; Marcin Moniuszko (Stem Cells International)
Muscular dystrophies (MD) are heterogeneous group of diseases characterized by progressive muscle dysfunction. There is a large body of evidence indicating that angiogenesis is impaired in muscles of MD patients. Therefore, induction of dystrophic muscle revascularization should become a novel approach aimed at diminishing the extent of myocyte damage. Recently, we and others demonstrated that administration of granulocyte colony-stimulating factor (G-CSF) resulted in clinical improvement of patients with neuromuscular disorders. To date, however, the exact mechanisms underlying these beneficial effects of G-CSF have not been fully understood. Here we used flow cytometry to quantitate numbers of CD34+ cells, endothelial progenitor cells, and different monocyte subsets in peripheral blood of pediatric MD patients treated with repetitive courses of G-CSF administration. We showed that repetitive cycles of G-CSF administration induced efficient mobilization of above-mentioned cells including cells with proangiogenic potential. These findings contribute to better understanding the beneficial clinical effects of G-CSF in pediatric MD patients.